Prenatal and postnatal evolution of isolated fetal splenic cysts. (1st April 2018) - Sauvageot, Camille; Faure, Jean‐Michel; Mousty, Eve; Flandrin, Anaïg; Forgues, Dominique; Prodhomme, Olivier; Fuchs, Florent
Abstract: Objectives: The aim of this study was to evaluate the prevalence, the prenatal, and postnatal evolution of isolated fetal splenic cysts. Methods: All cases of suspected fetal splenic cyst or abdominal unidentified cyst discovered during routine ultrasound scan, from 2007 to 2017, and referred to a French tertiary care center, were retrospectively collected. For each case, several prenatal parameters and postnatal evolution were reported. Results: Among 5450 cases of fetal anomalies, 14 patients (0.3%) had a prenatal diagnosis of fetal splenic cysts. Median gestational age at diagnosis was 30.1 weeks. A unique cyst was present in 78.6%, whereas 2 cysts were observed in 14.3% and 3 cysts in 7.1%. During the pregnancy, cysts remained the same (78.6%) or disappeared (21.4%). Ultrasound scans at 6 months of age found total disappearance of the cysts (36.4%), spontaneous reduction from 2 to 1 cyst (18.2%) or persistence of the cysts (45.4%). Conclusion: Fetal splenic cysts are rare images, always isolated, usually unique and mainly found during third trimester of pregnancy. Their evolution is to disappear spontaneously during pregnancy or at 6 months of age leaving only half of them to remain beyond that age but without any symptoms. Abstract : What's already known about this topic? Among splenic lesions, the more frequent are asplenia or polysplenia in case of fetal heterotaxia. Data regarding the prevalence, the diagnosis, and the prenatal or postnatal evolution of splenic cysts are very scarce in literature and mainly come from case reports. What does this study add? Congenital fetal splenic cysts are rarely discovered during the antenatal period. They are benign lesions, most often isolated and complications rarely occur. Their evolution is to disappear spontaneously during pregnancy or at 6 months of age leaving only half of them to remain beyond that age.